MONARDA - A VALUABLE SOURCE OF BIOLOGICALLY ACTIVE COM-POUNDS - V. A. Kharchenko; L. V. Bespalko; V. K. Gins; M. S. Gins; A. A. Baikov (Овощи России)
The experimental data on the content of water-soluble antioxidants, accumulation of vitamin C, and dry matter in plants of Monarda fistulosa L. and Monarda citriodora L. of the Lamiaceae family are presented in the article. As a result of comparative assessment the promising early ripening genotype №2 with high content of vitamin C was selected.